2017
DOI: 10.1111/bcpt.12907
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Optimum Mini‐doses of Glucagon and Insulin Levels when Treating Mild Hypoglycaemia in Patients with Type 1 Diabetes – A Simulation Study

Abstract: Hypoglycaemia remains the main limiting factor in type 1 diabetes management. We developed an insulin-dependent glucagon dosing regimen for treatment of mild hypoglycaemia based on simulations. A validated glucose-insulin-glucagon model was used to describe seven virtual patients with insulin pump-treated type 1 diabetes. In each simulation, one of ten different and individualized subcutaneous insulin boluses was administered to decrease plasma glucose (PG) from 7.0 to ≤3.9 mmol/l. Insulin levels were estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…These results are in accordance with Ranjan et al that worldwide presence of hypertension and diabetes mellitus exist in all age groups but it is more likely to occur in individuals with higher BMI [15]. Previously, increased BMI increases the risk of developing diabetes type 2.…”
Section: Glucagon Levels Normal Highsupporting
confidence: 92%
“…These results are in accordance with Ranjan et al that worldwide presence of hypertension and diabetes mellitus exist in all age groups but it is more likely to occur in individuals with higher BMI [15]. Previously, increased BMI increases the risk of developing diabetes type 2.…”
Section: Glucagon Levels Normal Highsupporting
confidence: 92%
“…However, several conditions may impair glucagon’s efficacy, i.e., low carbohydrate diets [16], exercise [17], ethanol intake [18], and hyperinsulinemia [19]. Therefore, if low-dose glucagon should be used in everyday treatment of mild hypoglycemia, a variable dosing regimen depending on these factors may be preferable as shown in a simulation study proposing an insulin-dependent glucagon dosing regimen for treatment of mild hypoglycemia [20].…”
Section: Discussionmentioning
confidence: 99%
“…Haymond et al also demonstrated that the glucose response to Xeris glucagon was blunted immediately after an insulin bolus compared with after an overnight fast 41 . In dual‐hormone closed‐loop studies, high ambient insulin concentrations were correlated with failure of glucagon to prevent and treat hypoglycaemia, 74,78,79 also shown in simulation studies 80 …”
Section: Potential Limitations Of Regular Glucagon Usementioning
confidence: 93%